Buckling of cracked cylindrical panels under axially compressive and tensile loads. (September 2015) - Seifi, Rahman; Saeidi Googarchin, Hamed; Farrokhi, Mohammad
Abstract: Buckling collapse of thin-walled structures under compression is one of the critical type of failures. These structures also may be locally buckled under tensile load with special conditions. In this paper, compressive and tensile buckling of thin cracked cylindrical panels are investigated. Effects of various factors such as the position, length and direction of crack, length, width and thickness of the panel and boundary conditions on the compressive and tensile buckling loads are determined. The results show that the dimensions of panels have lowest while characteristics of crack and closing to edges have greatest effects on the buckling load. Highlights: First mode of buckling more than higher modes affected by boundary conditions. Circumferential and axial cracks have respectively highest and lowest impacts. Buckling load of cracked panels is proportional to the square of thickness. Closing the crack to free boundaries reduces the buckling load.